2014
DOI: 10.1371/journal.pone.0094133
|View full text |Cite
|
Sign up to set email alerts
|

Empathy among Medical Students: Is There a Relation with Quality of Life and Burnout?

Abstract: BackgroundWe aimed to assess medical students' empathy and its associations with gender, stage of medical school, quality of life and burnout.MethodA cross-sectional, multi-centric (22 medical schools) study that employed online, validated, self-reported questionnaires on empathy (Interpersonal Reactivity Index), quality of life (The World Health Organization Quality of Life Assessment) and burnout (the Maslach Burnout Inventory) in a random sample of medical students.ResultsOut of a total of 1,650 randomly se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
168
4
65

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(262 citation statements)
references
References 56 publications
(97 reference statements)
25
168
4
65
Order By: Relevance
“…Some studies have found that burnout increases with each year of study among medical students [3538]. Other studies have reported an n-shaped curve with burnout climaxes in the middle phases of the medical curriculum [3941]. The results of the study presented here indicate that the different semesters show similar prevalence rates for burnout.…”
Section: Discussionsupporting
confidence: 59%
“…Some studies have found that burnout increases with each year of study among medical students [3538]. Other studies have reported an n-shaped curve with burnout climaxes in the middle phases of the medical curriculum [3941]. The results of the study presented here indicate that the different semesters show similar prevalence rates for burnout.…”
Section: Discussionsupporting
confidence: 59%
“…This does not support the work of Paro et al (2014), who found that personal accomplishment, rather than depersonalization, was predictive of the variance in perspective taking. Despite obvious differences between the studies in terms of location (Brazil) and target population (medical students), it is not clear why their findings would have differed from the current study.…”
Section: Exploring the Hypothesiscontrasting
confidence: 99%
“…Qualitative exploration could have enhanced understanding of the nature of the significant relationships, and further explored staff's perception of the utility of formulation. Alongside this, Paro et al (2014) highlighted the problem of social desirability bias in self-report measures of empathy, such as those used in the current study. Qualitative interviews may have given the researcher the opportunity to explore these issues; however, a mixed-method approach was beyond the resources of this project.…”
Section: Strengths and Limitationsmentioning
confidence: 93%
“…Students reporting lower levels of academic satisfaction presented higher burnout, supporting the hypothesis that students' depersonalization may be a possible explanation for lower academic satisfaction 78 which can undermine students' satisfaction and accomplishments in their future professional lives. 79,80 Psychological interventions focused on reducing burnout symptoms in pharmacy school, previously used to manage students' psychological distress and lack of academic motivation, 41,81,82 could have beneficial results in our population.…”
Section: Discussionsupporting
confidence: 59%